A systematic review on the effects of endometriosis on sexuality and couple's relationship - Norinho, P. (2021)
Background: Endometriosis is likely to affect sexuality and intimate relationships but the effect endometriosis has on partners remains overlooked and the existing studies show conflicting results. The effect of the disease and its treatment on the couple may be pronounced given the absence of an obvious cause or cure, the likelihood of chronic recurring symptoms, and the potential impact on both sex and fertility. Materials and methods: We followed the PRISMA guidelines to conduct this systematic review, which involved a database search of published available research related to the effects of endometriosis treatment on sexual function, couple's relationship and on the partner published between 2000 and 2020. Results: The studies considered revealed that women with endometriosis report a significant effect of the disease on sexuality and relationship. Also, most of the published studies suggest that the impact on partners may be profound, affecting many life domains including sex, intimacy and the relationship in general. Conclusions: Data suggests that male partners should not be overlooked in the treatment of endometriosis and that psychosocial support including sexual and couple therapy might be beneficial.